Clinical–Pathologic Characteristics and Long-term Outcomes of Left Flexure Colonic Cancer: A Retrospective Analysis of an International Multicenter Cohort. Issue 12 (December 2020) - Pedrazzani, Corrado; Turri, Giulia; Park, Soo Yeun; Hida, Koya; Fukui, Yudai; Crippa, Jacopo; Ferrari, Giovanni; Origi, Matteo; Spolverato, Gaya; Zuin, Matteo; Bae, Sung Uk; Baek, Seong Kyu; et al.
Abstract : BACKGROUND: Colorectal cancer seldom presents at the splenic flexure. Small series on left flexure tumors reported a high occurrence of negative prognostic factors called into question as causes of poor prognosis. However, because of the small number of cases, no definite conclusions can be drawn. OBJECTIVE: The aim of this study was to compare clinical-pathologic characteristics and short- and long-term outcomes of left flexure tumors with other colonic locations. DESIGN: This was a retrospective analysis of consecutive patients who underwent surgery for tumors at the splenic flexure. Each tumor was paired in a 1 to 1 fashion with a right-sided and sigmoid tumor. SETTINGS: The study was conducted in 10 international centers. PATIENTS: A total of 641 patients with left flexure tumors were included in the study. MAIN OUTCOME MEASURES: Overall survival and cancer-specific survival were measured. RESULTS: Left flexure tumors presented more frequently with stenosis (30.5%; p < 0.001), with lesions infiltrating beyond the serosa (21.9%; p = 0.001) and with a high rate of mucinous histology (8.8%; p = 0.001). Looking at long-term prognosis, no differences were observed among the 3 groups, both considering overall and cancer-specific survival. However, left flexure tumors recurred more frequently as peritoneal carcinomatosis (20.6%; p < 0.001). LIMITATIONS: This study was limited because of its retrospective nature. CONCLUSIONS: Although left flexure tumors display several negative prognostic factors, they are not characterized by a worse prognosis compared with other colon cancer locations. See Video Abstract at http://links.lww.com/DCR/B395 . CARACTERÍSTICAS CLÍNICO-PATOLÓGICAS Y RESULTADOS A LARGO PLAZO DEL CÁNCER DE COLON DE ÁNGULO IZQUIERDO: UN ANÁLISIS RETROSPECTIVO DE UNA COHORTE MULTICÉNTRICA INTERNACIONAL: ANTECEDENTES: El cáncer colorrectal rara vez se presenta en el ángulo esplénico. Pequeñas series sobre tumores de ángulo izquierdo informaron una alta incidencia de factores pronósticos negativos cuestionados como causas de mal pronóstico. Sin embargo, debido al pequeño número de casos, no se pueden sacar conclusiones definitivas. OBJETIVO: El objetivo de este estudio fue comparar las características clínico-patológicas, los resultados a corto y largo plazo de los tumores de ángulo izquierdo con otras ubicaciones de colon. DISEÑO: Análisis retrospectivo de pacientes consecutivos que se sometieron a cirugía por tumores en el ángulo esplénico. Cada tumor se emparejó de forma individual con un tumor del lado derecho y sigmoide. AJUSTES: El estudio se realizó en 10 centros internacionales. PACIENTES: Se incluyeron en el estudio un total de 641 pacientes con tumores del ángulo izquierdo. PRINCIPALES MEDIDAS DE RESULTADO: Supervivencia general y específica del cáncer RESULTADOS: Los tumores de ángulo izquierda se presentaron con mayor frecuencia con estenosis (30.5%, p <0.001), con lesiones infiltradas más allá de la serosa (21.9%, p = 0.001), y con una alta tasa de histología mucinosa (8.8%, p = 0.001). En cuanto al pronóstico a largo plazo, no se observaron diferencias entre los tres grupos, considerando la supervivencia general y específica del cáncer. Sin embargo, los tumores de ángulo izquierdo recurrieron con mayor frecuencia como carcinomatosis peritoneal (20, 6%; p <0, 001). LIMITACIONES: Este estudio fue limitado debido a su naturaleza retrospectiva. CONCLUSIONES: Aunque los tumores de ángulo izquierdo muestran varios factores pronósticos negativos, no se caracterizan por un peor pronóstico en comparación con otras ubicaciones de cáncer de colon. Consulte Video Resumen en http://links.lww.com/DCR/B395 . Abstract : Supplemental Digital Content is available in the text.